PERJANJIAN TINDAKAN MEDIS ANTARA DOKTER DENGAN PASIEN SEBAGAI BENTUK PELAYANAN PUBLIK - GEDE TUSAN ARDIKA (GANEC SWARA, 2019)
The purpose of this paper is to find out the procedure for making agreements in medical actions in health services between doctors and patients in handling medical measures. The research is a normative legal research study with an approach based on laws and regulations, a conceptual approach and a case approach.   From the results of the study it can be concluded that, the Agreement on Medical Action (informed consent) is carried out in accordance with statutory procedures, for that doctors are bound by professional code of ethics in carrying out their functions as medical personnel, so that in carrying out medical actions there must be an agreement and written agreement between the doctor and the patient. The legal consequences arising between the doctor and the patient after the medical action is carried out are in the form of legal responsibility, both in the form of civil, criminal and administrative law related to his profession.